"Building Together" in Baltimore? Corporate Megadevelopment and Coalitions for Community Power. Issue 4 (July 2022) - King, P. Nicole; Rich, Meghan Ashlin
We consider how various coalitions influence redevelopment projects in cities, especially as communities demand more inclusion in the development process. Based on qualitative research, we investigate the approval process for the 235-acre megadevelopment project at Port Covington in Baltimore, Maryland, and how stakeholders, including developers, community-based organizations, politicians, and impacted community members view the project, the tax increment financing (TIF) granted by the city, and community benefits agreements (CBAs). Community leaders leaned hard on the development corporation, demanding community and city-wide benefits before a TIF could be approved. We analyze the processes of the Port Covington CBA within the context of the political and economic dynamics of Baltimore. This case study adds to our understanding of how communities respond to corporate-led developments through coalition building, effectively gaining power in how elite governing regimes dictate development in cities.